Non-Muslim Students' Response to the Implementation of Multicultural Islamic Education in Higher Education: A Study on Inclusive Academic Environment - Mappayompa; Ati Sukmawati; Sahwan; Shabibah Binti Shaufit Affandi (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
The implementation of multicultural Islamic Education in Islamic-based universities often creates its own dynamics, especially for non-Muslim students who are part of an inclusive academic environment. This study aims to describe the response of non-Muslim students to learning Islamic Education in a multicultural context at Muhammadiyah Mataram University. This Islamic campus is open to diversity. Using a descriptive qualitative approach with a field research design, this study involved 75 non-Muslim students from seven study programs through a purposive sampling technique. Data were collected through semi-structured interviews, participatory observation in class and campus social spaces, and documentation of curriculum and academic policies. Data validity was maintained with a method triangulation strategy. Data analysis was conducted using Miles and Huberman's model, which involves the stages of data reduction, data presentation, and conclusion drawing. The results showed that the responses of non-Muslim students were mixed: some showed appreciation for the inclusive approach and universal values in Islamic Education, while others felt less engaged because the materials were considered too normative and exclusive. Factors such as the lecturer's pedagogical approach, the relevance of the material, and the social dynamics in a multicultural classroom greatly influenced their perceptions. This research recommendation encourages higher education policymakers to strengthen curricula and teaching methods that are dialogical, adaptive, and inclusive, thereby increasing tolerance and fostering peaceful coexistence in multicultural campus environments.